PENGARUH COMPETENCE BASED EDUCATION AND TRAINING (CBET) DAN MOTIVASI KERJA TERHADAP KINERJA PETUGAS SATUAN POLISI PAMONG PRAJA - Sutiyono, Agus (JIV-Jurnal Ilmiah Visi, 2010)
This research aimed to find out the influence of competence-based education and training (CbET) and motivation on the performance of civil service. This research was conducted from November 2008 to April 2009 at Dinas Ketrentaman dan Ketertiban DKI jakarta. A quasi method using stratified cluster random sampling was applied to involve 80 civil service out of 8000 members. The result of this study shows that (1) motivation influences the civil service’s performance, (2) the form of CBET influences the civil service’s performance; (3) the interaction between the training model and the motivation determines variations in civil service’s performance; (4) there are differences between those who join CBET and those who do not. Those who join CBET have higher motivation to perform better. It is expected that these research findings can be used as a guidance to produce a new concept and strategy in education development and training for civil service.